In defence of Criseyde : a consideration of the character as seen by Chaucer, Henryson and Shakespeare : a thesis presented in partial fulfilment of the requirements for the degree of Master of Arts in English at Massey University - Simmons, Marion Douglas (Massey University, 1981)
The love story of Troilus and Criseyde has had a continuous appeal since the appearance of its first version in the mid-twelfth century. The character of the heroine has proved controversial because of her unconventional behaviour. The earliest version by Benoît de Sainte Maure was used by Boccaccio as the basis for a love poem which expressed his personal grief at being separated from his beloved. Chaucer, in his turn, built on Boccaccio's work with a long narrative poem which incorporated many of the ideals of courtly love. His narrator is hopelessly biased towards Criseyde and lays the blame for any defects in her character on the reports of his authorities. We, too, are led by the narrator to sympathize with her by sharing in her motives and deliberations. A century later the Scottish poet, Henryson, produced an imaginary ending to Chaucer's poem in which the heroine contracted leprosy for her sins of the flesh and died after repenting of her past life. For nearly two hundred years this poem was believed to have been written as a sequel by Chaucer. Just over a century after Henryson's poem, Shakespeare produced the story as a drama interwoven with the military background of the Trojan war. The stage presentation, unpopular until this century, meant that the audience could see and hear Cressida's betrayal of Troilus in front of them, Shakeapeare also adopted a derisive tone towards courtly love which by his time was outmoded. Despite her extreme timidity, Chaucer's Criseyde is shown to betray Troilus for pragmatic reasons. This adds a realistic and opportunist dimension to her character. Chaucer implies ironically that we should not judge from appearances only. Henryson's Cresseid is revealed as excessively vain but she does gain self-knowledge through suffering and comes to terms with her fate before death. Whether Henryson viewed his heroine in pagan, courtly or Christian terms, is a point of disagreement among critics as the poem contains moral overtones. Shakespeare's Cressida is persuaded by Troilus to abandon her realism and surrender herself reluctantly to his idealism. Despite her later betrayal of him, her vows of love are sincerely made. Like most of the characters in the play she is unable to live up to her ideals. The heroine does not set out to ensnare either Troilus or Diomede but once they pursue her she cannot resist their advances. She reveals herself as being a victim of human frailty but her human weaknesses serve to endear herself to readers as a credible human being.
Keywords: Chaucer, Geoffrey, d.1400; Henryson, Robert, 1430?-1506?; Shakespeare, William, 1564-1616; Characters -- Cressida; Cressida (Fictitious character)